Paleoclimate. A better radiocarbon clock - Bard, E.; Rostek, F.; Menot-Combes, G. (Science, 2004)
id: 974; Bard, Edouard Rostek, Frauke Menot-Combes, Guillemette New York, N.Y. Science. 2004 Jan 9;303(5655):178-9.

Present status of radiocarbon calibration and comparison records based on Polynesian corals and Iberian Margin sediments - Bard, E.; Menot-Combes, G.; Rostek, F. (Radiocarbon, 2004)
In this paper, we present updated information and results of the radiocarbon records based on Polynesian corals and on Iberian Margin planktonic foraminifera. The latter record was first published by Bard et al. (2004a,b), with the subsequent addition of some data by Shackleton et al. (2004). These data sets are compared with the IntCal98 record (Stuiver et al. 1998) and with data sets based on other archives, such as varves of Lake Suigetsu (Kitagawa and van der Plicht 1998, 2000), speleothems from the Bahamas (Beck et al. 2001), and Cariaco sediments (Hughen et al. 2004). Up to 26,000 cal BP, the Iberian Margin data agree within the errors of the other records. By contrast, in the interval between 33,000 and 41,000 cal BP, the Iberian Margin record runs between the Lake Suigetsu and Bahamian speleothem data sets, but it agrees with the few ImCal98 coral data and the Cariaco record.
956zfTimes Cited:30Cited References Count:33

Radiocarbon calibration beyond 20,000 B.P. by means of planktonic foraminifera of the Iberian Margin - Bard, E.; Rostek, F.; Menot-Combes, G. (Quaternary Research, 2004)
We present a new set of 14C ages obtained by accelerator mass spectrometry (AMS) on planktonic foraminifera from a deep-sea core collected off the Iberian Margin (MD952042). This site, at 37°N, is distant from the high-latitude zones where 14C reservoir age is large and variable. Many independent proxies — alkenones, magnetic susceptibility, ice-rafted debris, foraminifera stable isotopes, abundances of foraminifera, pollen, and dinoflagellates — show abrupt changes correlative with Dansgaard-Oeschger and Heinrich events of the last glacial period. The good stratigraphic agreement of all proxies — from the fine to the coarse-size fractions — indicates that the foraminifera 14C ages are representative of the different sediment fractions. To obtain reliable 14C ages of foraminifera beyond 20,000 14C yr B.P., we leached the shells prior to carbonate hydrolysis and subsequent analysis. For a calendar age scale, we matched the Iberian Margin U37K′ profile with that of Greenland Summit δ18O. Both are proxies for temperature, which in models varies synchronously in the two areas. The match creates no spurious jumps in sedimentation rate and requires only a limited number of tie points. Except for ages older than 40,000 14C yr B.P., Greenland's GISP2 and GRIP records yield similar calendars. The 14C and imported calendar ages of the Iberian Margin record are then compared to data — from lacustrine annual varves and from corals and speleothems dated by U–Th — previously used to extend the calibration beyond 20,000 14C yr B.P. The new record follows a smooth pattern between 23,000 and 50,000 cal yr B.P. We find good agreement with the previous data sets between 23,000 and 31,000 cal yr B.P. In the interval between 33,000 and 41,000 cal yr B.P., for which previous records disagree by up to 5000 cal yr, the Iberian Margin record closely follows the polynomial curve that was previously defined by an interpolation of the coral ages and runs between the Lake Suigetsu and the Bahamian speleothem data sets.
id: 401
Keywords: Dansgaard-Oeschger events; Heinrich events; Laschamp magnetic excursion; Last glacial cycle; North Atlantic; Radiocarbon calibration